Zamia orinoquiensis (Zamiaceae, Cycadales), a new species from the western Orinoquía region of Colombia - Calonje, Michael; Betancur, Julio; Lindstrom, Anders; Lopez-Gallego, Cristina; Castro, Jonatan; Castro, Cristian; Niño, Santos Miguel; Canelon Barraez, Daniela (Phytotaxa, 2022)
Zamia orinoquiensis Calonje, Betancur & A.Lindstr., a new species from the western Orinoquía region of Colombia is described and illustrated. The species is segregated from and compared to Z. muricata Willd., the latter which is morphologically recharacterized, illustrated, and recircumscribed to include populations from tropical dry forest and tropical moist forests in the Lara-Falcón Formation and the Cordillera de la Costa natural regions of Venezuela, as well as the Serranía de Macuira in La Guajira, Colombia. Zamia orinoquiensis is morphologically distinguished from Z. muricata by its leaves bearing fewer, coriaceous (vs. papyraceous) leaflets, eophylls with 2 (vs. 4) leaflets, pollen strobili that are brown to reddish brown (vs. cream to tan) with larger microsporophylls bearing more numerous microsporangia, and ovulate strobili that are dark brown to black (vs. dark olive green to olive brown) at maturity.